(Photo)electrocatalytic Versus Heterogeneous Photocatalytic Carbon Dioxide Reduction. Issue 9 (13th September 2021) - Bellardita, Marianna; Loddo, Vittorio; Parrino, Francesco; Palmisano, Leonardo
Abstract: The front cover artwork is provided by the authors, University of Palermo (Italy). The image depicts the synergic coupling of the electrocatalytic system (yellow wire) with a photocatalytic one (blue wire), represented by the weaving of the two wires together. The coupled system is used for the photoelectrocatalytic reduction of carbon dioxide to form light organic species with possible simultaneous hydrogen production. Read the full text of the Review at 10.1002/cptc.202100030 . Abstract : "The photoelectrocatalytic method can mitigate/overcome the weaknesses of both photocatalysis and electrocatalysis and minimize the simultaneous formation of H2 . In fact, it allows to increase the efficiency of CO2 reduction and direct the selectivity towards certain products…" This and more about the story behind the front cover can be found in the Review at 10.1002/cptc.202100030 .